Cardiac diastolic function of 8–9-year-old singletons following fresh or frozen embryo transfer compared to naturally conceived – a cardiac magnetic resonance study. (25th November 2020) - Mizrak, I; Asserhoej, L.L; Jensen, R.B; Lund, M.A.V; Heldarskard, G.F; Kjaer, A.S.L; Greisen, G; Vejlstrup, N; Madsen, P.L; Pinborg, A
Abstract: Background: Epigenetics may alter the cardiovascular system of children conceived after assisted reproductive technology (ART). Singletons born after frozen embryo transfer (FET) are more likely to be large for gestational age and fresh embryo transfer (ET) are at risk of being small for gestational age. Children conceived after ART may have endothelial dysfunction, and high body mass index and arterial blood pressure (ABP). Such changes may be associated with cardiac diastolic dysfunction. Purpose: We investigate whether children conceived after fresh ET and FET are at risk of cardiac changes including left ventricular (LV) diastolic dysfunction. Methods: 150 9-year-old singletons have been recruited in a cardiac magnetic resonance imaging study (all scanned by April 2020). 50 children were born after natural conception (NC); 50 children after FET; and 50 children after fresh ET. Left atrium (LA) maximal volume, LA early emptying fraction (LAEEF), LV peak filling rates (PFR) and the peak ejection rate (PER)/PFR ratio are reported to assess the diastolic function. Results: Preliminary data analyzed in a blinded manner from 59 children show no differences in ambulatory ABP, LV and right ventricular ejection fraction, end-diastolic and end-systolic volumes, stroke volumes and LV mass between the groups. With respect to LV diastolic function, no differences were seen in LA maximal volume and LAEEF; but the Fresh ET group tended to have lower PFR with a resultant PER/PFR ratio now increasing above unity compared to the other groups. Conclusion: Preliminary data suggest a possible trend towards diastolic dysfunction in children born after fresh ET. If the lack of significant difference in heart function between NC and FET can be ascertained in the full cohort, this is reassuring. Funding Acknowledgement: Type of funding source: Private grant(s) and/or Sponsorship. Main funding source(s): Novo Nordisk Foundation